Metabolomic and pharmacologic analyses of brain substances associated with sleep pressure in mice. (April 2022) - Suzuki-Abe, Haruka; Sonomura, Kazuhiro; Nakata, Shinya; Miyanishi, Kazuya; Mahmoud, Asmaa; Hotta-Hirashima, Noriko; Miyoshi, Chika; Sato, Taka-Aki; Funato, Hiromasa; Yanagisawa, Masashi
Highlights: It is difficult to separate the metabolomics effect of stress in sleep deprivation studies alone. Whole-brain levels of betaine and imidazole dipeptides change in two distinct mouse models of high sleep pressure. Central injection of imidazole dipeptides promotes non-REM sleep, implicating the compounds in sleep/wake regulation. Abstract: Sleep pressure, the driving force of the homeostatic sleep regulation, is accumulated during wakefulness and dissipated during sleep. Sleep deprivation (SD) has been used as a method to acutely increase animal's sleep pressure for investigating the molecular changes under high sleep pressure. However, SD induces changes not only reflecting increased sleep pressure but also inevitable stresses and prolonged wake state itself. The Sik3 Sleepy mutant mice ( Sleepy ) exhibit constitutively high sleep pressure despite sleeping longer, and have been useful as a model of increased sleep pressure. Here we conducted a cross-comparison of brain metabolomic profiles between SD versus ad lib slept mice, as well as Sleepy mutant versus littermate wild-type mice. Targeted metabolome analyses of whole brains quantified 203 metabolites in total, of which 43 metabolites showed significant changes in SD, whereas three did in Sleepy mutant mice. The large difference in the number of differential metabolites highlighted limitations of SD as methodology. The cross-comparison revealed that a decrease in betaine and an increase in imidazole dipeptides are associated with high sleep pressure in both models. These metabolites may be novel markers of sleep pressure at the whole-brain level. Furthermore, we found that intracerebroventricular injection of imidazole dipeptides increased subsequent NREM sleep time, suggesting the possibility that imidazole dipeptides may participate in the regulation of sleep in mice.